2020
DOI: 10.1021/acssuschemeng.0c01154
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation and Flotation to Recover Protein-Enriched Biomasses from Shrimp Boiling and Peeling Process Waters: A Case Study

Abstract: A novel integrated process for the recovery of protein-enriched biomasses from shrimp boiling water (SBW) and shrimp peeling water (SPW) was investigated by combining flocculation (F) and dissolved air flotation (DAF) into an F-DAF process. Alginate and carrageenan were used as flocculants. It was found that the protein yield from SPW and SBW in the F-DAF process was 68−97% and 26− 45%, respectively. This led to a reduction in protein content of the influent SBW and SPW (12.4 and 1.4 g/L, respectively) by up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“… 2 8 In addition, our own group has reported on flocculation combined with flotation to recover protein-enriched biomasses from shrimp boiling water (SBW) and peeling water (SPW). 9 , 10 However, still very little is known about the variations in the nutrient composition of shrimp process waters over an extended production period. A broad nutrient characterization as well as insight into potential toxic elements and shelf life would aid the implementation of new and already reported recovery tools for proteins, fatty acids, antioxidants, and flavor molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 8 In addition, our own group has reported on flocculation combined with flotation to recover protein-enriched biomasses from shrimp boiling water (SBW) and peeling water (SPW). 9 , 10 However, still very little is known about the variations in the nutrient composition of shrimp process waters over an extended production period. A broad nutrient characterization as well as insight into potential toxic elements and shelf life would aid the implementation of new and already reported recovery tools for proteins, fatty acids, antioxidants, and flavor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…There are thus strong incentives to minimize nutrient losses taking place along with the current treatments of these massive amounts of water as wastewaters. So far, a few studies have reported on the recovery of volatile compounds, bioactive peptides, and astaxanthin from shrimp process waters by employing techniques such as ultrafiltration, reverse osmosis, and nano filtration together with osmotic evaporation. In addition, our own group has reported on flocculation combined with flotation to recover protein-enriched biomasses from shrimp boiling water (SBW) and peeling water (SPW). , However, still very little is known about the variations in the nutrient composition of shrimp process waters over an extended production period. A broad nutrient characterization as well as insight into potential toxic elements and shelf life would aid the implementation of new and already reported recovery tools for proteins, fatty acids, antioxidants, and flavor molecules.…”
Section: Introductionmentioning
confidence: 99%
“…We believe though that the advantage of using incubation treatments to minimize lipid oxidation during ensilaging outweighs the slightly reduced rate of protein hydrolysis as the final silage will have a much higher quality. Further, the proteins lost into the incubation solution can be recovered by using techniques such as flocculation combined with flotation or ultrafiltration, as reported elsewhere 39 41 , ensuring as complete use as possible of the herring raw material.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, the food and beverage industries are one of the largest consumers. The seafood processing industry plays a key role in water consumption, as 2% of all freshwater consumed in the food and beverage industry [2] is used throughout the processing steps, such as washing, cooking, freezing, disinfection and, floor cleaning.…”
Section: Introductionmentioning
confidence: 99%
“…The European Directive 98/83/EC allows water reuse in the industrial process [7]. This approach brings further revenues to the seafood processing industries, both from the added-value food components [2] and from the reduction of the wastewater discharge costs.…”
Section: Introductionmentioning
confidence: 99%